MULTIFUNCTIONAL COATINGS TO PREVENT SPREAD OF INFECTIOUS DISEASES - Abu Jarad, Noor (My University, 2024)
Healthcare-associated infections present an escalating worldwide issue, further intensified by the emergence of antimicrobial resistance and the spread of pathogens on surfaces. Current infection prevention methods have shown limited effectiveness, leading to several health issues, an overuse of antibiotics, and a continuous threat of surface recontamination. In response, extensive research has focused on bioinspired omniphobic smart coatings that effectively reduce the contact area available for pathogen attachment, achieved through an increase in surface roughness and apparent surface energy. This thesis introduces a new class of an omniphobic spray-coating, featuring hierarchical structured polydimethylsiloxane (PDMS) microparticles coated with gold nanoparticles, encompassing primary microscale (~0.23 𝜇m) and secondary nanoscale (~5 nm) buckyball and labyrinth wrinkles. This substrate-independent coating efficiently repels a wide range of liquids, including pathogens, even under harsh conditions like high temperatures, ultraviolet (UV) exposure, and abrasions. Repellency tests comparing coated and uncoated gloves revealed that uncoated gloves spread contamination to 50 secondary surfaces, while coated gloves transferred fewer bacteria and viruses to just three and two surfaces, respectively. The investigation extended to the coating's biocidal capabilities, incorporating gold nanoparticles functionalized with mercapto-silane to create a "Repel and Kill" coating. This process initiates chemisorption through thiol-gold bonding, allowing for the formation of diverse surface structures, including three-dimensional self-assembly, multilayers, and island structures. These modifications significantly enhance the roughness and hydrophobicity of the gold nanoparticles, amplifying their biocidal effectiveness. The wrinkled structure of PDMS contribute to repellency, while the functionalized gold nanoparticles play a crucial role in the antimicrobial property. This enhancement was evident in the antibacterial tests, which exhibited an immediate 99.90% reduction in bacterial adhesion for both MRSA and Pseudomonas aeruginosa (P. aeruginosa), followed by an additional 99.70% and 99.90% reduction in bacterial growth after 8 hours for MRSA and P. aeruginosa, respectively. Moreover, the coating's antiviral properties were confirmed, demonstrating a 98% reduction in the transfer of the bacterial virus Phi6. Recognizing the role of hospital fabrics as potential reservoirs for infection transmission, primarily due to their ability to sustain bacterial growth for extended periods, especially in the presence of bodily fluids, we took further steps to modify the wrinkled PDMS microparticles. This involved the incorporation of silver nanoparticles, capped with a positively charged ligand known as branched polyethyleneimine (bPEI). Additionally, we integrated a colorimetric sensor, giving rise to the "Repel, Kill, and Detect" smart coating. The transition of color from blue to green-yellow provided a tangible indicator of contamination detection based on the acidic mileu of the biofilms. To evaluate its realworld effectiveness, we conducted simulations of infection transmission in hospital environments, resulting in a remarkable reduction in pathogen adhesion from urine and feces by 99.88% and 99.79%, respectively, compared to uncoated fabrics. To further enhance the validation of our results, we employed a powerful deep learning network architecture, that determined whether the surfaces are contaminated or safe. In the face of evolving health challenges, this coating emerges as a resilient and adaptable solution, promising to enhance overall safety and alleviate the burden of infectious diseases.
Keywords: healthcare-acquired infections, anti-microbial, anti-viral, biofilms, hierarchical structures, omniphobic coating, infection detection, optical sensing